PERKEMBANGAN EMBRIO DAN PERFORMA AWAL LARVA TIGA SPESIES IKAN TOR INDONESIA - Wahyulia Cahyanti; Deni Radona; Anang Hari Kristanto (BERITA BIOLOGI, 2020)
Tor fish is a potential local fish. It has social, economic and religious value and contains albumin which is equivalent to snake head fish. As a local fish cultivation potential, an accurate description of the early development stages of this species, will have value for ichthyologists and can facilitate cultivation efforts to increase production. This study aims to understand the embryology of three tor fish species and to determine the condition of larval performance at the beginning of hatching. The division process begins when the cell nucleus is divided into 2 blastomers, then continues to reach 32 cells in the first 10 hours after fertilization. At 10–20 hours after fertilization the eggs enter the morula, blastula and gastrula phases. After 20 hours, the organogenesis stage occurs. Tor douronensis hatched the fastest, more than 100 hours after fertilization (0.70–0.80 cm length, 0.0073 g weight and 8.40±1.83% abnormality). Tor soro over 120 hours (length 0.80–0.90 cm, weight 0.0125 g and abnormality 2.47±0.12%) and Tor tambroides above 140 hours after fertilization (length 1,00–1,09 cm, weight 0,0146 g and abnormality 2.93±0.31%). It can be concluded that there is no difference in the process of embryogenesis of the three species until the gastrula stage. The difference arises in the organogenesis phase, where the Tor douronensis organ develops most rapidly, followed by Tor soro and Tor tambroides.